Vincetoxicum siamicum sp. nov. (Asclepiadeae, Asclepiadoideae, Apocynaceae), a rheophyte from northeastern Thailand and preliminary observation on its in situ pollen germination - Kidyoo, Aroonrat (Phytotaxa, 2016)
Vincetoxicum siamicum A.Kidyoo, newly described here, is a rheophytic herb growing in dense clumps near or in streams in northeastern Thailand. Here I provide a diagnosis and detailed description of this new species, as well as illustrations and photographs. Several characters of V. siamicum are compared with those of V. stauntonii, considered to be a close relative. These two species display consistent differences in leaf arrangement and corona structure. A comparison with other rheophytic species, V. glaucescens, V. hydrophilum, V. riparium, V. verticillatum, is also provided. They differ in several traits: shape, size and texture of leaves, hairiness of corolla lobes, branching pattern of inflorescences and elevations at which they occur. In addition, in situ pollen germination observed in the flowers of V. siamicum is reported.